Main Problems the Creation of Universal Theory the Computer Science - Trokhimchuck, Petro Pavlovych (My University, 2024)
The main problems of the creation of the universal theory of computer science are discussed. Short historical analysis of this question is represented. Issues related to what such a theory should be and what problems it should solve are discussed. The issue of the need to introduce a system approach in information theory is analyzed. It showed that this theory must be variant theory of everything in a global sense and must be theory of open type. We analyzed six criteria, which such theories must satisfy. An example of such a theory is polymetric analysis, a theory of variable measure and hierarchy. This concept includes the procedure for choosing the operating base (mathematical transformations) and the corresponding computational construct (connectedness parameter). Two components of this method theory of informative calculation and the hybrid theory of systems allow for resolving the main problems of modern computer science. Thus, the theory of information calculations was used for the some problems of computer arithmetic). The hybrid theory of systems was used for resolution the S. Beer centurial problem in cybernetics (the problem of information complexity) and the classification of information according to its computational complexity. Other questions of application this concept in computer science are discussed too.
Keywords: open systems; computer science; S. Beer centurial problem; universal theory